Countering the Machiavellian: Power, Intrigue, and Resistance in the Soliloquies of Shakespeare's Hamlet. - Roy, Lekha (IUP Journal of English Studies, 2017)
Taking as a framework the theory of power as "domination over," a theory propounded by social critics such as Machiavelli (1961), Hobbes (1968), Foucault (1980), Weber (1986), and Bordieu (1994), this paper attempts to decipher the dilemma evident in the soliloquies of Shakespeare's Hamlet as the result of an unresolved conflict between a Machiavellian (external) political world and a Montaignian (internal) world guided by Platonic ideals. The paper traces how the changed dialectics of reason and power at the court in Denmark leave a chasm in Hamlet's personality, through which the relation of the past and present surface as a disjointed continuum, disturbing the metaphysical structure of temporality that gives meaning to action. Treating the play as a political statement on the discourse of power, it analyzes how a dissonance between the ideals that govern Hamlet's inner world and the political machinations that rule the court at Denmark leads to a crippling psycho-spatial imbalance that makes action impossible, and warns of the reification of power and the return to a pre-Renaissance Machiavellian structure of ethics that endangered England at the turn of the century.